Teachers and Students Perceptions on Hybrid Learning in Informatics Department: Challenges and Benefits - Rhetno Wardhani, Dyah; Kuncoro, Adhityo (Jurnal Pendidikan Impola, 2024)
Hybrid learning has been adopted by colleges and universities after the COVID-19 pandemic era. This study aims to investigate the challenges and benefitsof hybrid learning in Informatics engineering department. Teachers and students’ perceptions were gathered by semi-structured interview to gain deeper information. Five teachers and five students were selected from Informatics department. The data gathered from semi-structured interview showed that both teacher and students experienced some challenges and benefits, which are technological challenges, engagement strategies, support and training, and flexibility and autonomy. This study result could be a beneficial insight for further research regarding hybrid learning.